High post-fledging survival and site persistence using mark-resight methodology for Oregon Vesper Sparrows in the Willamette Valley, Oregon - Bob Altman; Joel Geier; Sarah M Rockwell (Avian Conservation and Ecology)
The ecology of the post-fledging period for small passerine birds is one of the least known stages of the avian life cycle with high rates of mortality for many species. We examined post-fledging survival and site persistence of Oregon Vesper Sparrows ( Poocetes gramineus affinis ) based on extensive temporal and spatial implementation of mark-resight methodology in western Oregon, 2017–2021. Our analyses focused on a comparison of descriptive apparent survival estimates (i.e., return rates) uncorrected for detectability and modeled apparent survival estimates corrected for detectability using Program MARK. Modeled survival estimates were only slightly higher than descriptive survival estimates at three weeks (0.754 and 0.689), six weeks (0.659 and 0.617), and nine weeks (0.629 and 0.561). Both estimates were lowest at three weeks post-fledging (0.754 and 0.689), and higher in weeks 3–6 (0.874 and 0.897), and weeks 6–9 (0.954 and 0.893). The best supported model included an effect of fledgling age in weeks on survival probability, and additive effects of site, effort, and week of season on detection probability. There was a live resight during the post-fledging period of at least one bird from 94.9% of the successfully fledged nests. Site persistence greater than 50 days was 0.838. Mean site persistence was 78.1 days and longest site persistence for an individual bird was 115 days. Our results suggest that an extensive mark-resight effort can address detectability concerns and provide an approximation of true post-fledging survival estimates. Our post-fledging survival estimates are the highest reported for a grassland bird, and yet they contrast with the expectations of the methodology and the literature on post-fledging survival of grassland birds, which is mostly derived from radio-tracking methodology. These results along with recent meta-analyses from other researchers raise concerns about unreported and unknown but expected mortality in grassland nestlings and fledglings from additive predation due to radio-tracking attachments and devices.